Chemoenzymatic Access to Chiral Tetrols Produced by Thiamine Diphosphate Dependent Benzaldehyde Lyase. Issue 46 (15th October 2018) - Zecevic, Damir; Germer, Philipp; Walter, Lydia; Gauchenova, Ekaterina; Müller, Michael
Abstract : Highly functionalized polyol building blocks have been synthesized by means of stereoselective chemoenzymatic C–C bond formation followed by stereoselective reduction. Catalysis by thiamine diphosphate (ThDP) dependent benzaldehyde lyase (BAL) with glyceraldehyde acetonide as acceptor substrate gave highly stereoenriched polyols such as (1 S, 2 S, 3 R )‐1‐phenylbutane‐1, 2, 3, 4‐tetrol (1 ), the 3, 4‐protected anti ‐1, 2‐diol5, and the precursor of both compounds, 2‐hydroxyketone4 . Abstract : A straightforward access to chiral tetrols by means of a chemoenzymatic approach. This highly diastereoselective ( de > 99 %) tetrol synthesis is performed in two reaction steps and is based on two commodity chemicals.